(untitled) (Journal of history, 2019)
The research topic actualizes the spirituality and mental traditions of the Kazakhs, on the example of the little-known book of I. Altynsarin. The purpose and main directions of research are dictated by the content of the Head of State’s article «The Seven Facets of the Great Steppe», the program «Rouhani Zhangyru», which gave impetus to the idea of studying the sacral values of the people and the works of predecessors who left a noticeable trace on their preservation and synthesis. About the scientific and practical significance of the work «says» our choice of an artifact created by Arabic graphics as a subject of research and related social connections as its object. The Soviet period excluded the development of historians associated with religion; the study will replenish this sector of scientific research. The textbooks on the basics of Islam and translations published now in the republic will be possible in practice to be compared with their forerunner. The research is based on the methods of historical science, dialectical method, historicism, comparative analysis, verification of sources, quantitative, applicable in general and separately to each source and historiographical work, as well as ethnology and anthropology methods: accumulation and systematization, visualization; sociological methods: observations and sampling. The main results of the source analysis, against the background of foreign historiography, were the conclusions about the undoubted authorship of Altynsarin for the first official textbook on the basics of Islam, which corresponded to the cultural needs and ethnicity of Kazakh students. The value of the conducted research is consistent with the world historiography of the theme of missionary work and the preservation of local cultural traditions; the study for the first time reveals the stages of creating the first Kazakh textbook for secular education on the basics of religion, created in the second half of the 19th century.